2015
DOI: 10.1109/mce.2015.2393007
|View full text |Cite
|
Sign up to set email alerts
|

Überveillance, the web of things, and people: What is the culmination of all this surveillance?

Abstract: H istorically, telecommunications companies have measured voice and data traffic for reasons related to service dimensioning and engineering management. Today, personalized devices make it possible to understand not only the requirements for the capacity needed in a network but also household and individual usage patterns. This has changed the way that companies now market their products and services and sell directly to individuals. Beyond marketing is the intimate knowledge gathered of why people do things, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…The research model shown in Figure 1 is proposed. Since the pervasive consumer electronics (Michael et al., 2015) are not yet widely used and still represent a specific lifestyle choice, three categories of habits and personal characteristics that could influence a person’s decision to use MI were proposed. The first category, online activities , includes the individual’s behavior on SM, which gives an indication of their level of activity on the Web.…”
Section: Methodsmentioning
confidence: 99%
“…The research model shown in Figure 1 is proposed. Since the pervasive consumer electronics (Michael et al., 2015) are not yet widely used and still represent a specific lifestyle choice, three categories of habits and personal characteristics that could influence a person’s decision to use MI were proposed. The first category, online activities , includes the individual’s behavior on SM, which gives an indication of their level of activity on the Web.…”
Section: Methodsmentioning
confidence: 99%
“…The famous Delphic maxim "know thyself" takes on new connotations, as does the well-known Cartesian philosophical statement, "I think, therefore I am." In the context of uberveillance, this AI artefact (in effect, a blackbox [2], [3]) masquerades as omnipresent and omniscient surveillance [30], [45], [46], [47], which depending on your place in the axis of access [48], [49], [50], may be unable to be turned on and off [4]. In some instances, the AI may even over-ride your decisions based on whether you have been categorized as someone living with certain conditions (e.g., dementia) or retaining a certain status (e.g., parolee).…”
Section: In Image and Likenessmentioning
confidence: 99%
“…To carry the analogy further, big data aims to reconstruct the very personal, precisely customized, and hitherto private thought processes of a consumer. Big data explores details of the relationship between people's intent and actual behavior and how people interact with objects around them [28].…”
Section: Meso: Machine Learning Marketing and Biologicalization-based...mentioning
confidence: 99%
“…It is that which Orwell stated was the only thing left that was sacred, that space between our skull where we were once free to roam, think, feel, and reflect without scrutiny. New pervasive technologies have the ability to extract thoughts, removing all barriers for marketing and consumption [28].…”
Section: Need For Socio-technical Interventionmentioning
confidence: 99%